BS EN 61557-12 AMD1. Electrical safety in low voltage distribution systems up to 1 000 V AC and 1 500 V DC. Equipment for testing, measuring or monitoring of protective measures. Part 12. Power metering and monitoring devices (PMD) (15th November 2019) - British Standards Institution,
No abstract available